Influence of nanoclay particles modification by polyester-amide hyperbranched polymer on the corrosion protective performance of the epoxy nanocomposite. (March 2015) - Ganjaee Sari, M.; Ramezanzadeh, B.; Shahbazi, M.; Pakdel, A.S.
Highlights: Nanoclay particles were modified with polyester-amide hyperbranched polymer. Epoxy/clay nanocomposites were prepared using modified clay particles. Surface modification enhanced the clay particles exfoliation properties. Surface modified clay particles enhanced corrosion resistance of the epoxy coating. Abstract: Surface modification of nanoclay particles was carried out by various amounts of polyester-amide hyperbranched polymer (HBP). Thermal gravimetric analysis and X-ray diffraction analysis were performed to estimate the efficiency of the HPB grafting on the clay particles. Epoxy/clay nanocomposites were prepared by addition of 1 wt.% unmodified and modified clays. The corrosion protection properties of the nanocomposites were evaluated by electrochemical impedance spectroscopy (EIS). Results revealed that surface modification of the clay particles by HBP caused significant enhancement of the epoxy coating corrosion resistance especially when the 'polymer/clay' ratios were 10/1 and 5/1.